2014
DOI: 10.1371/journal.pone.0115492
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Childhood Environmental Exposures and the Subsequent Development of Crohn's Disease in the Western Cape, South Africa

Abstract: BackgroundEnvironmental factors during childhood are thought to play a role in the aetiolgy of Crohn's Disease (CD). However the association between age at time of exposure and the subsequent development of CD in South Africa is unknown.MethodsA case control study of all consecutive CD patients seen at 2 large inflammatory bowel disease (IBD) referral centers in the Western Cape, South Africa between September 2011 and January 2013 was performed. Numerous environmental exposures during 3 age intervals; 0–5, 6–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Nine examined exposure during infancy early childhood and 8 included non-white populations 13, 20-22, 24, 26 . The included literature comprised 5,391 cases of CD, 2,504 of UC, and 179 with IBD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine examined exposure during infancy early childhood and 8 included non-white populations 13, 20-22, 24, 26 . The included literature comprised 5,391 cases of CD, 2,504 of UC, and 179 with IBD.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 10, 8, and 3 studies provided information on association between home or bedroom sharing and CD, UC, or IBD respectively (Table 1) 12, 13, 15, 19, 20, 24, 28-32 . Five examined exposure during early childhood and six were in a non-white population.…”
Section: Resultsmentioning
confidence: 99%
“…Disease characteristics of the CD cohort have been described in detail elsewhere [26]. Healthy controls, not related to the CD cases, were identified from the same populations giving rise to the CD cases; the recruitment method for control subjects has been described elsewhere [27].…”
Section: Design and Settingmentioning
confidence: 99%
“…In a second report, the same authors identified a significant risk-association between second-hand cigarette smoke exposure during childhood (0–5 and 11–18 years) and risk of future CD development. Moreover, an exposure to second-hand cigarette smoke during the age interval 11–18 years, was found to be independently associated with CD risk [ 27 ].…”
Section: Introductionmentioning
confidence: 99%